Forecasting for the optimal numbers of COVID-19 infection to maintain economic circular flows of Thailand - Chanamart Intapan; Chukiat Chaiboonsri; Pairach Piboonrungroj (Economies, 2021)
We evaluated the movement in the daily number of COVID-19 cases in response to the real GDP during the COVID-19 pandemic in Thailand from Q1 2020 to Q1 2021. The aim of the study was to find the number of COVID-19 cases that could maintain circulation of the country's economy. This is the question that most of the world's economies have been facing and trying to figure out. Our theoretical model introduced dynamic stochastic general equilibrium (DSGE) models with a special emphasis on Bayesian inference. From the results of the study, it was found that the most reasonable number of COVID-19 cases that still maintains circulation of the country's economy is about 3000 per month or about 9000 per quarter. This demonstrates that the daily number of COVID-19 cases significantly affects the growth of Thailand's real GDP. Economists and policymakers can use the results of empirical studies to come up with guidelines or policies that can be implemented to reduce the number of infections to satisfactory levels in order to avoid Thailand lockdown. Although the COVID-19 outbreak can be suppressed through lockdown, the country cannot be locked down all the time.
Keywords: 330; COVID-19; Bayesian; DSGE; number of coronavirus disease 2019 cases; Thailand's economy circulation; the optimal number of COVID-19 cases